Pengaruh Lingkungan kerja,Kepemimpinan dan Motivasi Terhadap Semangat Kerja Guru - Dedeh Imam Fatmasari (El-Idaarah, 2021)
This study aims to determine the effect of work environment, leadership, motivationon teacher morale. After testing, it is concluded that work environment, leadership, motivation,have a significant effect on teacher morale. Simultaneously it is known that there is a significantinfluence between work environment, leadership, motivation and collectively towards the moraleof the teacher.Based on the statistical test, an adjusted R square (R2) of 0.660 or 66.0% was obtained, whichindicates that 66.0% of changes in teacher morale variables can be explained by variables ofwork environment, leadership, motivation, while the remaining 31.2% is explained by othervariables outside the model. The result of 0.660 shows that the relationship between theseindependent variables together on the teacher work spirit variable has a strong andunidirectional relationship. Meanwhile, each of the independent variables affecting teachermorale are:Y = 0.776 + 0.611 X2 + 0.125 X3 + 0.461 X4 means a constant. Based on the t test, it was foundthat the variables of competence and enthusiasm had no effect on teacher morale, and othervariables had an effect. For the F test, the results show that together the independent variableshave an effect on the morale of teachers in SMK RADEN PATAH Mojosari.